Model Evaluation of the Microbial Metabolic Processes in a Hydrogen-Based Membrane Biofilm Reactor for Simultaneous Bromate and Nitrate Reduction - Minmin Jiang; Yuanyuan Zhang; Jie Zhang; Xingru Dai; Haixiang Li; Xuehong Zhang; Zhichao Wu; Junjian Zheng (Membranes, 2022)
The H2-based membrane biofilm reactor (H2-MBfR) has been acknowledged as a cost-effective microbial reduction technology for oxyanion removal from drinking water sources, but it remains unknown how the evolution of biofilm characteristics responds to the changing critical operating parameters of the H2-MBfR for simultaneous bromate (BrO3−) and nitrate (NO3−) elimination. Therefore, an expanded multispecies model, applicable to mechanistically interpret the bromate-reducing bacteria (BRB)- and denitrifying bacteria (DNB)-dominated metabolic processes in the biofilm of the H2-MBfR, was developed in this study. The model outputs indicate that (1) increased BrO3− loading facilitated the metabolism of BRB by increasing BRB fraction and BrO3− gradients in the biofilm, but had a marginal influence on NO3− reduction; (2) H2 pressure of 0.04 MPa enabled the minimal loss of H2 and the extension of the active region of BRB and DNB in the biofilm; (3) once the influent NO3− concentration was beyond 10 mg N/L, the fraction and activity of BRB significantly declined; (4) BRB was more tolerant than DNB for the acidic aquatic environment incurred by the CO2 pressure over 0.02 MPa. The results corroborate that the degree of microbial competition for substrates and space in the biofilm was dependent on system operating parameters.